#TITLE_ALTERNATIVE# - NURDANY MAGETSARI (NIM 25106004), RADEN
The purpose of this research is studying the dynamics of suspended sediments in North Java coasts, represented by Bekasi and Indramayu sites. The study of suspended sediment dynamics is carried out by identifying seabed response due to currents and waves effects. The steps performed in this research are: 1) estimation of suspended sediments concentration based on acoustic echo intensity, 2) characterization of hydrodynamic conditions (i.e. currents, tide and waves) using hydro-acoustic instruments, 3) identification of seabed response in relation to the hydrodynamic conditions. Primary data that used in this research are measured using 600 and 1000kHz Aquadoppler. Estimation of suspended sediments concentration showed quiet good result, but estimation model is very site-specific. Currents pattern on both locations are highly related to near shore morphology. In Bekasi site, current pattern stratification occurred at near shore. Mostly, currents moved toward North East. In offshore area, the tidal current movement is dominant. Result in Indramayu sea site showed very strong East current movements in near shore area. In both sites, currents speed in near shore area is stronger than in offshore area. Sea turbidity in Bekasi is higher (2500mg/l) rather than in Indramayu (0.05mg/l); this is caused by the existed sediment supply from river mouth (Citarum) nearby near shore site measurement. This is proved by the higher level of suspended sediments concentration at surface rather than at seabed. At offshore area in both sites, sediments that supplied the water column came from seabed. A suspended sediment profile developed at seabed is higher than the surface. While currents and waves effects mainly caused temporal variability of sediment concentration in both sites. Daily changes of suspended sediment concentration are strongly correlated with daily tides.